Bristol Cathedral
Buttresses for the vault, which elsewhere had been concealed in the space above the aisle or had been allowed to spring out into the open above the aisle roof, are incorporated within the aisle itself at Bristol. This novel and skillful structural system was to repeated in England, though there may be some connection with the later hall churches of Germany. The use of high molded arches, without capitals was, however, of great importance to future English work.